(3TQM GdQSGFds - (3GdcGXej, GdJSJQj, YHO GdMSjf Hf eMeO Hf CSO Gddg, J (B1336(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3bhdg(B:.. (3aGYde Cf Gdecda EPG GdJaJ Edi Mce TQYj(B...s
(3BNQgG (B:s
(3acPdc Ef de jOd Odjd Ybdj Ch fbdj Ydi dRhe GdGMJjGW(B... (3hdG Odjd ZjQg jbJVj hLhH GdGMJjGW YOG bGYOI hLhH OaY GdVQQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B54s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs